The RNA World The Nature of Modern RNA suggests a Prebiotic RNA - Gesteland, Raymond F;Ed. Cech Thomas R;Ed (Cold Spring Harbor monograph series, 43., 2006)
"Recent studies on the activities of RNA in the cell have revolutionized our understanding of the many roles played by this molecule. The first two editions of The RNA World (1993, 1999) shed light on the pre-biotic era dominated by this versatile molecule, and provided an overview of the state of RNA research at the time. The new third edition of The RNA World updates this perspective, describing the vast array of newly discovered roles for RNA in the modern world. The updated original chapters are supplemented with new chapters on RNA-protein complexes, snRNPs and snoRNPs, telomerase RNA, RNAi, microRNAs, noncoding RNA, and many other subjects. This book is essential reading for anyone interested in the biology of nucleic acids and gene regulation and a valuable resource for teaching these concepts."--BOOK JACKET.